PEMODELAN LOG TOTAL ORGANIC CARBON (TOC) MENGGUNAKAN METODE PASSEY, REGRESI MULTI LINEAR DAN NEURAL NETWORK - Jamaluddin Jamaluddin; Maria Maria; Emi Prasetyawati Umar (Sekolah Tinggi Teknologi MIGAS, 2022)
Laboratory analysis has proven the Talang Akar Formation as a source rock that is relatively rich in organic content, but the availability of laboratory data is very limited to determine the quantity of organic material in a regional basin area, which is the main objective in this research. Therefore, a simple proven and accurate method is needed to model the TOC (organic carbon content) throughout the borehole is needed. TOC log modeling was performed using the Passey method, multilinear regression and neural network. Based on the modeling results, the multilinear regression method got better results to be applied to the Talang Akar Formation.